PENGEMBANGAN MODEL LATIHAN PASSING SEPAKBOLA PADA CLUB GENSUS JUNIOR DESA CUPAK KECAMATAN DANAU KERINCI - Josep Josep; Anton Komaini (JURNAL STAMINA, 2018)
From observations, researchers found problems with passing, especially at lower passing. The researcher saw no development of the passing training model. The purpose of this study was to analyze the need for the development of variations in passing towards the effectiveness of developing soccer passing and developing models of passing training in football. The type of this research is research is Research and Development (R & D). The population is 23 people. The sampling technique is taken by total sampling. The sample in this study amounted to 23 people. Data retrieval techniques were given a passing model on the Junior Gensus football club in Cupak Village, Lake Kerinci District, Kerinci Regency. Based on the results of data analysis shows that the training method used is then done with a normality test with a significant level  = 0.05 with L count = 0.1336 <Ltable = 0.190. The value of L count is smaller than L table so it is normal. And the model of passing training is very feasible to use with an expert test with a percentage of 82.81%